2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6942902
|View full text |Cite
|
Sign up to set email alerts
|

Online interactive perception of articulated objects with multi-level recursive estimation based on task-specific priors

Abstract: To successfully manipulate in unknown environments, a robot must be able to perceive degrees of freedom of objects in its environment. Based on the resulting kinematic model and joint configurations, the robot is able to select and adapt actions, recognize their successful completion and detect failure. We present an RGB-D-based online algorithm for the interactive perception of articulated objects. The algorithm decomposes the perception problem into three interconnected levels of recursive estimation. The es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…We distinguish two main approaches to visual tracking: based on a known shape model of the object [2], and based on sufficient texture using point features [4] or dense optical flow [5,7]. While tracking with a known model is more accurate, texturebased approaches are also applicable to unknown objects.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…We distinguish two main approaches to visual tracking: based on a known shape model of the object [2], and based on sufficient texture using point features [4] or dense optical flow [5,7]. While tracking with a known model is more accurate, texturebased approaches are also applicable to unknown objects.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work we have shown that tracking can also greatly benefit from a known kinematic structure [4].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, SLAM [48] couples localization and mapping in a recursive estimation loop to solve the joint problem more effectively. More recently, combining interaction and perception led to advances in robot perception [6,27,34].…”
Section: A Modularity Vs Integrationmentioning
confidence: 99%